2001
DOI: 10.1046/j.1365-3156.2001.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and case management of clinical malaria in the primary health services of a rural area in south‐eastern Tanzania

Abstract: SummaryMalaria control continues to rely on the diagnosis and prompt treatment of both suspected and con®rmed cases through the health care structures. In south-eastern Tanzania malaria is one of the leading causes of morbidity and mortality. The absence of microscopic examination in most of the health facilities implies that health workers must rely on clinical suspicion to identify the need of treatment for malaria. Of 1558 randomly selected paediatric consultations at peripheral health facilities throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 11 publications
10
84
1
Order By: Relevance
“…It has been reported that there was a reduction in the intensity of P. falciparum transmission over the previous ten years. The incidence of fever in Sudan is low; 1.8% is associated with P. falciparum [13]. The results of this study are in concordance with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that there was a reduction in the intensity of P. falciparum transmission over the previous ten years. The incidence of fever in Sudan is low; 1.8% is associated with P. falciparum [13]. The results of this study are in concordance with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…The use of presumptive diagnosis in the management of malaria commonly leads to diagnostic inaccuracies and over-diagnosis of malaria [28] [29]. This could endanger patients that have more deadly conditions such as Lassa fever or Yellow fever, by being erroneously treated for malaria while delaying the initiation of correct treatment for some of these potentially fatal diseases; whose prognoses is positively affected by early initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis alone is not specific and results in inappropriate use of antimalarial drugs. [1][2][3][4][5] Increasing drug resistance to inexpensive antimalarial drugs and the higher cost of alternative medications has led to an increased focus on malaria diagnosis. Rapid diagnostic tests (RDTs) were developed to improve the quality of malaria diagnosis in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%